2012
DOI: 10.1007/s00382-012-1350-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep-ocean heat uptake and equilibrium climate response

Abstract: We integrate the coupled climate model ECHAM5/MPIOM to equilibrium under atmospheric CO2 quadrupling. The equilibrium global-mean surface-temperature change is 10.8 K. The surface equilibrates within about 1,200 years, the deep ocean within 5,000 years. The impact of the deep ocean on the equilibrium surface-temperature response is illustrated by the difference between ECHAM5/MPIOM and ECHAM5 coupled with slab ocean model (ECHAM5/SOM). The equilibrium global-mean surface temperature response is 11.1 K in ECHAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
152
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(185 citation statements)
references
References 39 publications
21
152
2
1
Order By: Relevance
“…This implies a multi-millennial timescale for the SO response to GHG forcing, consistent with GCM simulations 6,7 . Though we may not yet know the full mechanisms driving SO trends, these results suggest that the observed SO cooling and sea-ice expansion over recent decades must be interpreted against a background of very gradual GHGinduced warming -instead of the rapid warming seen in the Arctic.…”
supporting
confidence: 81%
“…This implies a multi-millennial timescale for the SO response to GHG forcing, consistent with GCM simulations 6,7 . Though we may not yet know the full mechanisms driving SO trends, these results suggest that the observed SO cooling and sea-ice expansion over recent decades must be interpreted against a background of very gradual GHGinduced warming -instead of the rapid warming seen in the Arctic.…”
supporting
confidence: 81%
“…However, a comparison of the difference in temperature response to upper-and deep-ocean heat uptake and its contribution to the relationship between net radiative flux change (N) and global temperature change ( T ) in Geoffroy et al (2013) indicated that the method of of fitting two separate linear models to the early and subsequent (N, T ) data gives a good approximation of T g eq , F and α as they have been calculated here. A study by Li et al (2013) also found that, using the Gregory plot methodology, T g eq was estimated to within 10 % of its ac- tual value, obtained by running the simulation very close to equilibrium (∼ 6000 years). However, this was using the ECHAM5/MPIOM model, meaning that it is not necessarily also true for HadCM3.…”
Section: Gregory Plotsmentioning
confidence: 82%
“…There have been speculations that the recent hiatus in planetary mean surface temperature rise indicates that the climate system is less CO 2 sensitive than previously thought. On the other hand, new studies have demonstrated that decadal atmospheric warming is considerably masked by equatorial Pacific variability in heat uptake and release (36)(37)(38)(39).…”
Section: Forecasting the Next El Niñomentioning
confidence: 99%